“It opened my eyes”: parents’ experiences of their child receiving an anxiety disorder diagnosis - Davey, E; Creswell, C; Percy, R; Reardon, T (SAGE Publications, 2022)
Anxiety disorders are the most common mental health disorders among children, however there is limited guidance on the process of assessing child anxiety disorders and sharing diagnostic outcomes with families. This study aimed to identify aspects of the diagnostic process that are helpful and/or unhelpful for families, and ways to mitigate any potential negative consequences of receiving a child anxiety disorder diagnosis. A qualitative study was conducted with parents of 11 children (aged 7-12 years) with a primary diagnosis of an anxiety disorder, identified through a child mental health service. We used an inductive thematic analysis approach. Elements of the diagnostic process considered helpful or less helpful for families related to four themes: clarity and insight, being heard, the anxiety label and access to support. Findings illustrate the importance of sharing diagnoses compassionately in the context of ensuing treatment, and the benefits of providing families with personalised verbal and written diagnostic information, that is tailored for both parents and children.